Experimental investigation on the characteristics of tire wear particles under different non-vehicle operating parameters. (October 2020) - Chang, Xiang-dong; Huang, Hai-bo; Jiao, Run-nan; Liu, Jin-peng
Abstract: Tire wear particles are an important non-exhaust contributor of urban particulate matter, which could cause environmental pollution and threaten human health. In this paper, tire-road rolling wear experiments were carried out using a self-made test rig. The size distribution and generation mechanism of wear particles under different non-vehicle operating parameters (treadwear, road roughness and relative humidity) were investigated. The results show that the size of the tire wear particles is an approximately normal distribution in most cases, and tires with good wear resistance produce fewer particles. The quantity of fine particles (<10 μm) is much higher under water lubricating. Temperature has a strong influence on the particle size and even changes the wear mechanism. The high temperature increases the probability of large particles. Additionally, high temperature produces more tire wear particles and further increases the surface wear during the rapid rise of the tread temperature. The major wear mechanisms of the tire rubber are abrasive wear and fatigue wear, which significantly influence the particle size. Furthermore, this study can provide basic data for the reduction of the secondary hazards of tire wear particles. Graphical abstract: Image 1 Highlights: The rolling wear experiments of tires were carried out using a self-made testing apparatus. The size distribution and generation mechanism of the tire wear particles were analysed. The quantity of fine wear particles (<10 μm) is much higher under water-lubricated condition. The road roughness has obvious effect on the tread temperature during the wear tests. The fatigue wear of the tire tread is easier to produce smaller wear particles than abrasive wear.